2019
DOI: 10.1183/23120541.00178-2018
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive airway pressure adherence declines with age in elderly obstructive sleep apnoea patients

Abstract: Obstructive sleep apnoea (OSA) is an important public health problem with an estimated prevalence of 5–15% in the general population. This increases with age, peaking at 20–25% in individuals aged >65 years. This high prevalence of OSA in the elderly will presumably continue to grow as a consequence of the increasing longevity of the general population [1]. It is therefore not surprising that there is a steady increase in the percentage of patients >65 years of age referred to sleep units for suspicion of OSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Our results confirmed the results of previous smaller studies [ 29 , 30 ] addressing adherence to CPAP therapy in elderly patients with OSA, but also produced contradictory results to some other studies [ 20 ]. In our study, elderly people aged 70–79 years adhered to PAP therapy at least as well as the middle-aged patients.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our results confirmed the results of previous smaller studies [ 29 , 30 ] addressing adherence to CPAP therapy in elderly patients with OSA, but also produced contradictory results to some other studies [ 20 ]. In our study, elderly people aged 70–79 years adhered to PAP therapy at least as well as the middle-aged patients.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, there are not only health related but also social and economic incentives to actively treat elderly OSA patients. However, the data of CPAP adherence in the elderly patients are conflicting [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Patient characteristics such as age ( 17 , 18 ), gender ( 17 , 19 ), race ( 20 ), and smoking status ( 21 ) could affect adherence, although these factors were not consistent determinants of CPAP adherence ( 12 ). For example, the adherence to CPAP positively correlated with age was reported in a retrospective study ( 17 ), but a large cohort study showed a negative correlation with age, particularly in those aged >75 years old, which may be due to the body sickness, sleeping time, or sleep quality of the elderly can affect the adherence of CPAP ( 18 ). Smokers caused decreased CPAP adherence compared to non-smokers ( 21 ), which is attributed to those smokers being more susceptible to upper airway discomfort, the greater severity of OSA, and as a result, less likely to take advice from healthcare providers ( 21 ).…”
Section: Factors Associated With Continuous Positive Airway Pressure ...mentioning
confidence: 99%
“…Not only is it important that MFTs be aware of these changes, but also MFTs can play a role in highlighting the specific sleep hygiene recommendations as discussed above. In addition, some may use a CPAP; as adherence rates are typically poor (Martinez-Garcia et al, 2019), MFTs could collaborate and follow-up with other health care providers to address compliance issues from a BPSS perspective.…”
Section: Developmental Considerationsmentioning
confidence: 99%